Neuronal Polarity: Positive and Negative Feedback Signals - Takano, Tetsuya; Funahashi, Yasuhiro; Kaibuchi, Kozo (Frontiers in Cell and Developmental Biology, 2019)
Establishment and maintenance of neuronal polarity are critical for neuronal development and function. One of the fundamental questions in neurodevelopment is how neurons generate only one axon and several dendrites from multiple minor neurites. Over the past few decades, molecular and cell biological approaches have unveiled a large number of signaling networks regulating neuronal polarity in cultured hippocampal neurons and the developing cortex. Emerging evidence reveals that positive and negative feedback signals play a crucial role in axon and dendrite specification. Positive feedback signals are continuously activated in one of minor neurites and result in axon specification and elongation, whereas negative feedback signals are propagated from a nascent axon terminal to all minor neurites and inhibit the formation of multiple axon, thereby leading to dendrite specification and maintaining neuronal polarity. This current insight provides a holistic picture of the signaling mechanisms underlying neuronal polarization during neuronal development. Here, our review highlights recent advancements in this fascinating field, with a focus on the positive and negative feedback signals as key regulatory mechanisms underlying neuronal polarization.